Influence of microbiota-driven natural antibodies on dengue transmission - Wu-Chuang, Alejandra; Rojas, Alejandra; Bernal, Cynthia; Cardozo, Fátima; Valenzuela, Adriana; Romero, Cristina; Mateos-Hernández, Lourdes; Cabezas-Cruz, Alejandro (Frontiers in Immunology, 2024)
Dengue has had a significant global health impact, with a dramatic increase in incidence over the past 50 years, affecting more than 100 countries. The absence of a specific treatment or widely applicable vaccine emphasizes the urgent need for innovative strategies. This perspective reevaluates current evidence supporting the concept of dual protection against the dengue virus (DENV) through natural antibodies (NAbs), particularly anti-α-Gal antibodies induced by the host's gut microbiome (GM). These anti-α-Gal antibodies serve a dual purpose. Firstly, they can directly identify DENV, as mosquito-derived viral particles have been observed to carry α-Gal, thereby providing a safeguard against human infections. Secondly, they possess the potential to impede virus development in the vector by interacting with the vector's microbiome and triggering infection-refractory states. The intricate interplay between human GM and NAbs on one side and DENV and vector microbiome on the other suggests a novel approach, using NAbs to directly target DENV and simultaneously disrupt vector microbiome to decrease pathogen transmission and vector competence, thereby blocking DENV transmission cycles.